Innovativeness of Poland’s Economy – Conditions and Prospects for Development - Kasperkiewicz, Witolod (Comparative Economic Research. Central and Eastern Europe, 2012)
This paper considers the very important issue of innovativeness of Poland’s economy with particular attention given to its innovation strategy. The major thesis of the paper argues that the growth of innovativeness of the Polish economy requires structural, institutional, and financial changes in the long run. The analysis is based on the set of indices reported by the European Commission, the Information Technology and Innovation Foundation, Washington, and UNU – MERIT Maastricht University. The structure of the article is as follows: the introduction is followed by an assessment of the level of innovativeness of Poland’s economy, explanation of the reasons of poor innovativeness, and then the conditions for innovation in Poland are outlined with particular emphasis on strategic aspects and the final part presents synthetic conclusions derived from the analysis.